The Philosophy of Justice in Business Law: A Comparative Study of Ethical Values in Ghana and Indonesia’s Constitutional Frameworks - Kurniawan, I Gede Agus; Putu Aras Samsithawrati; Disantara, Fradhana Putra; Nutakor, Briggs Samuel Mawunyo; Thuong, Mac Thi Hoai (Indonesian State Law Review, 2025)
The role of the philosophy of justice in business law as a moral and normative foundation that ensures economic activities are not only oriented towards technical efficiency but also uphold principles of justice such as distributive, commutative, and fairness. The philosophy of justice is closely related to constitutional values because the constitution not only regulates legal norms but also contains ethics and social goals that must be reflected in business regulations. Not only regulates legal norms but also contains ethics and social goals that must be reflected in business regulations. This research aims to analyze the philosophy of justice in business law in relation to the principles and values in the constitution and ethical values of a country, with a legal comparison between Indonesia and Ghana. This research is a normative legal study with a conceptual, comparative legal, and legislative approach. The research findings affirm that a comparative study with Ghana shows that although both countries emphasize the importance of ethical and just economic governance based on constitutional values, their approaches differ. Indonesia has a structured system based on the constitution and the interpretation of the Constitutional Court, whereas Ghana relies on a pluralistic legal framework and sectoral regulations that are not fully integrated with the constitution. This difference highlights the importance of the role of the constitution and the judiciary in realizing fair, transparent, and sustainable business law.